If only I were--- - Sommer, Carl, 1930-; James, Kennon (Houston : Advance Pub., 1997)
As she tries being one creature after another, from a cat to an elephant trainer, Missy the mouse discovers that everyone has problems and that she can find happiness as herself.
Keywords: Mice -- Fiction; Animals -- Fiction; Self-acceptance -- Fiction